The toxic effects of combined aflatoxins and zearalenone in naturally contaminated diets on laying performance, egg quality and mycotoxins residues in eggs of layers and the protective effect of Bacillus subtilis biodegradation product. (April 2016) - Jia, Ru; Ma, Qiugang; Fan, Yu; Ji, Cheng; Zhang, Jianyun; Liu, Tao; Zhao, Lihong
Abstract: The toxic effect of aflatoxins (AF) and zearalenone (ZEA) and their combination on laying performance, egg quality and toxins residues in eggs, as well as the efficacy of Bacillus subtilis biodegradation product (BDP) for ameliorating these effects in layers were evaluated. Layers were submitted to a two phase experiment. The first phase was an intoxication period (18–23 wk) with birds fed 7 (3 × 2 + 1) diets (3 treatments with mycotoxins: AF (123.0 μg/kg), ZEA (260.2 μg/kg), or AF + ZEA (123.0 + 260.2 μg/kg); 2 treatments with or without BDP (1000 g/t); and a control group contained no toxins nor BDP). The next phase was a recovery period (24–29 wk) in which birds were fed a toxin-free diet. In the intoxication period, AF and AF + ZEA groups exhibited lower egg production, feed intake and shell thickness, and higher AFB1, AFB2 and AFM1 residues as compared with the control group. In addition, AF and ZEA exerted synergistic effects on egg production and feed intake. Moreover, AF alone or combined with ZEA had a continuous toxic effect on laying performance in the recovery phase. Addition of BDP offset these negative effects, showing that BDP has a protective effect on layers fed contaminated diets. Highlights: Aflatoxins alone or combined with zearalenone results in depressed laying performance and egg quality of hens. Residue of aflatoxin B2 in eggs was a more sensitive index to reflect the hazards of aflatoxins in eggs. Combined aflatoxins and zearalenone showed synergistic effects for decreasing laying performance and egg quality in birds. Aflatoxins alone or combined with zearalenone had a continuous toxic effect on laying performance after toxin removal. Combined Bacillus subtilis counteracted these adverse effects of toxins.